Determinants of non-performing loans: evidence from the South African banking system - Ntabanyane, Puseletso (My University, 2022)
The aim of the study was to investigate the determinants of non-performing loans (NPLs) in South African banks. The determinants of NPLs included macroeconomic, microeconomic (bank specific characteristics) and behavioral finance (influence of customer sentiments). The health of an economy is driven by the health of the financial system in that economy. NPLs can have an impact on the health of an economy as rising NPLs could lead to bank failures. This in turn may lead to fearful public sentiment, bank runs and the ultimate collapse of the financial system. The study explores the macroeconomic determinants of NPLs, the bank specific determinants of NPLs and the behavioural finance. The study uses a panel data regression model in analysing the data and the data were sourced from the South African Reserve Bank (SARB), Orbis BankFocus, The World Bank and Bureau of Economic Research (BER). The data spans a sample period of between 2006-2020 and the geographic focus is mainly on South African banks (17 in total). The study aims to add to the existing literature. The study aims to do so by adding the behavioral finance aspect, consumer sentiment will be used as a variable that explains the behavioural finance. Behavioural finance as a determinant of NPLs can be used in future research papers.
A research report submitted in partial fulfilment of the Degree of Master of Commerce in Finance to the Faculty of Commerce, Law and Management, School of Economics and Finance, University of the Witwatersrand, Johannesburg, 2022